Functional N-cycle genes in soil and N2O emissions in tropical grass-maize intercropping systems - Grassmann, Camila S. [UNESP]; Mariano, Eduardo [UNESP]; Diniz, Priscila P.; Borges, Beatriz M.F.; Borges, Clovis D.; Tsai, Siu M.; Rosolem, Ciro A. [UNESP] (Elsevier, 2022)
There is evidence that forage grasses such as Megathyrsus and Urochloa can suppress nitrification, with direct or indirect consequences on soil inorganic N dynamics and nitrous oxide (N2O) emissions. However, the influence of soil chemical properties on the dynamics of functional N-genes and losses of N in maize (Zea mays L.) intercropped with forage grasses under N fertilization is poorly understood. In this study, soil samples and N2O emissions were analyzed from a field experiment in which maize (fertilized or not with ammonium-based fertilizer) was intercropped with Guinea grass (M. maximus cv. Tanzânia), palisade grass (U. brizantha cv. Marandu), and ruzigrass (U. ruziziensis cv. Comum). Soil N-cycle microorganisms [16S rRNA of bacteria and archaea, nifH (gene encoding N2-fixing bacteria), ammonia-oxidizing bacteria (AOB) and archaea (AOA), nirS (encoding nitrite reductase), and nosZ (encoding nitrous oxide reductase)] were influenced by forage grass, N fertilization, and sampling time, but no evidence of biological nitrification inhibition was found. Palisade grass was associated with a higher abundance of nifH (7.0 × 105 gene copies g−1 soil, on average) in the absence of N compared with the other grasses (4.3 × 105 gene copies g−1 soil, on average). Nitrogen fertilization increased the abundance of AOB but not AOA. Furthermore, N2O flux was influenced by AOB, water-filled pore space, and N fertilization, whereas the cumulative N2O emission and fertilizer-induced emission factor (0.36%, on average) were not affected by the grasses. In conclusion, this study reveals the strong dominance of AOB under ammonium supply, potentially stimulating N2O emissions in maize-forage grass intercropping systems.
Keywords: Biological nitrification inhibition; Megathyrsus; N fertilization; qPCR; Urochloa; Zea mays L.